Pengaruh aspek afektif terhadap prestasi akademik mahasiswa - Achmad Efendi; Dahlia (Jurnal Pendidikan Ekonomi (JUPE), 2025)
This study is motivated by the phenomenon that student academic achievement is not only determined by cognitive abilities, but also influenced by affective aspects such as motivation, self-confidence, emotional regulation, and academic engagement. This study aims to determine and analyze the influence of affective aspects on student academic achievement. This study uses a quantitative approach with a survey method. The number of samples used was 185 students using the slovin formula, a simple linear regression analysis tool which became the analysis technique.  The results showed that there is a positive and significant influence between affective aspects on student academic achievement. This finding also shows the importance of maximizing affective aspects in improving academic achievement and supporting student academic success.